1988
DOI: 10.1111/j.1365-2958.1988.tb00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of the nucleoprotein gene from a virulent British field isolate of transmissible gastroenteritis virus and its expression in Saccharomyces cerevisiae

Abstract: Subgenomic mRNA from a virulent isolate of porcine transmissible gastroenteritis virus (TGEV) was used to produce cDNA which was sequenced. Two non-overlapping open reading frames (ORFs) were identified. The largest, encoding a polypeptide of 382 amino acids (relative molecular mass (Mr) 43,483), was shown to be the viral nucleoprotein gene. The second ORF, found 3' to the larger ORF, encodes a polypeptide of 78 amino acids (Mr 9068) which has yet to be assigned to a viral product. The nucleoprotein gene was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 48 publications
(25 reference statements)
0
31
0
Order By: Relevance
“…Specific restriction fragments from TGEV cDNA clones were separated on agarose gels, purified using Geneclean (Stratech Scientific) and labelled with [~-32p]dATP (Amersham) (Maniatis et al, 1982). TGEV and PRCV subgenomic mRNA species were denatured with 6 M-glyoxal, electrophoresed into 1% agarose gels, Northern-blotted onto Biodyne membranes (P/N BNNG3R 1.2 p.m; PAL) and hybridized to 32P-labelled TGEV cDNA fragments (Britton et al, 1988a.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific restriction fragments from TGEV cDNA clones were separated on agarose gels, purified using Geneclean (Stratech Scientific) and labelled with [~-32p]dATP (Amersham) (Maniatis et al, 1982). TGEV and PRCV subgenomic mRNA species were denatured with 6 M-glyoxal, electrophoresed into 1% agarose gels, Northern-blotted onto Biodyne membranes (P/N BNNG3R 1.2 p.m; PAL) and hybridized to 32P-labelled TGEV cDNA fragments (Britton et al, 1988a.…”
Section: Methodsmentioning
confidence: 99%
“…2) indicating that the PRCV-derived PCR fragment was 200 bp larger than expected from the mRNA analysis. The 1350 bp PRCV cDNA fragment was cloned into pUC13 and positive clones were identified using 32p_ labelled TGEV cDNA from ORF-3b as described by Britton et al (1988a). The plasmid DNA from a positive clone, pKP-1, was used for DNA sequencing.…”
Section: Cloning Of the P R C V Genome Between Oligonucleotides 51 Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The extreme 3' non-coding region comprised an 8 nucleotide sequence conserved in coronaviruses, and ended in a poly(A) stretch. Pairwise alignment of the PRCV sequence data with those available for the three different TGEV strains Purdue 115 , FS772/70 (Britton et al, 1988a(Britton et al, , b, 1989 and Miller (Wesley et al, 1989;Wesley, 1990) revealed a very high level of homology. Thus, 96% overall homology was found between PRCV and TGEV Purdue strains at both the nucleotide and amino acid level.…”
Section: Dna Sequencing and Analysismentioning
confidence: 99%
“…Data from the proposed amino acid sequence for ORF-4 (Britton et al, 1988) were used to synthesize three oligopeptides (produced by Dr T. Doel, AFRC Institute for Animal Health, Pirbright Laboratory, U.K.) as shown in Fig. 2.…”
mentioning
confidence: 99%